R&D-driven medical progess, health care costs, and the future of human longevity - Sebastian Böhm; Volker Grossmann; Holger Strulik (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2017)
In this paper we set up an overlapping generations model of gerontological founded human aging that takes the interaction between R&D-driven medical progress and access to health care into account. We use the model to explore potential futures of human health and longevity. For the baseline policy scenario of health care access, the calibrated model predicts substantial future increases in health and life expectancy, associated with rising shares of health expenditure in GDP. Freezing the expenditure share at the 2020 level by rationing access to health care severely reduces potential gains in health, longevity and welfare. These losses are greatest in the long run due to reduced incentives for medical R&D. For example, rationing is predicted to reduce potential gains of life-expectancy at age 65 by about 4 years in the year 2050. Generally, and perhaps surprisingly, young individuals (i.e. those who save the most health care contributions through rationing) are predicted to suffer the greatest losses in terms of life expectancy and welfare.
Keywords: H50; I10; C60; 330; Longevity; Medical R&D; Morbidity; Health Care; Rationing